2018
DOI: 10.1590/1981-22562018021.180008
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care: A proposal for undergraduate education in Medicine

Abstract: Objective: to propose essential competencies for the teaching of palliative care on undergraduate Medicine courses. Method: a documentary analysis of the literature on general competencies in palliative care was initially carried out, to construct a framework with suggestions of essential competencies for undergraduate education in Brazil. The elaborated material was then presented individually to eight professionals from a range of areas for analysis. All the professionals had specialized training in palliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 24 publications
1
12
0
9
Order By: Relevance
“…It is observed that Palliative Care began in Brazil only in the 80's, causing delay or even the inexistence of this issue in the curricular curricula of health care courses, which may justify the lack of knowledge presented in the speeches of the participants. 16 On the other hand, similar research was carried out with 159 Nursing professionals in a Spanish hospital of third level, pointing out, as a result, that the participants show a sufficient knowledge about the Palliative Care, a fact that can be justified by Spain include in the graduation, Palliative Care with a heterogeneous study plan on the subject, in addition to a postgraduate program. 17 It is understood, for many health professionals, the impossibility of cure as a justification for the execution of limited care, which confronts the principles of Palliative Care in which professionals must offer a support system that enables the patient to live as actively as possible, until the moment of his death, offering a support system to assist the family members.…”
Section:  Understanding Palliative Carementioning
confidence: 77%
See 1 more Smart Citation
“…It is observed that Palliative Care began in Brazil only in the 80's, causing delay or even the inexistence of this issue in the curricular curricula of health care courses, which may justify the lack of knowledge presented in the speeches of the participants. 16 On the other hand, similar research was carried out with 159 Nursing professionals in a Spanish hospital of third level, pointing out, as a result, that the participants show a sufficient knowledge about the Palliative Care, a fact that can be justified by Spain include in the graduation, Palliative Care with a heterogeneous study plan on the subject, in addition to a postgraduate program. 17 It is understood, for many health professionals, the impossibility of cure as a justification for the execution of limited care, which confronts the principles of Palliative Care in which professionals must offer a support system that enables the patient to live as actively as possible, until the moment of his death, offering a support system to assist the family members.…”
Section:  Understanding Palliative Carementioning
confidence: 77%
“…The difficulty of health professionals in dealing with death in the current literature is highlighted, highlighting that it is associated to the traditional teaching method, centered on the cure and rehabilitation of the disease, in this way, often decontextualized from reality. 16 It is added that both the family members and the multiprofessional team suffer with the death of the child and, thus, seek to find mechanisms to face loss and mourning. 25 It is warned that in Palliative Care, understanding about the various forms of spirituality can be a positive strategy for English/Portuguese J Nurs UFPE online., Recife, 13(1):126-36, Jan., 2019 132…”
Section: []My I'm Sad I Cry I Cry I Cry I Go Out There I Do mentioning
confidence: 99%
“…The inserted content should be based on consistent scienti c literature and demanded research time from the authors. However, the competencies required for basic palliative care are broad and numerous, and the degree of depth of the approach in medical training has rarely been described in the literature [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Embora não tenhamos estabelecidas as competências em cuidados paliativos para a graduação médica, essa questão vem sendo discutida. 10,11 A seguir, consta a proposta dos autores em relação aos pré-requisitos:…”
Section: Sobre Os Pré-requisitosunclassified
“…Conhece os conceitos e princípios de CP: há inserção progressiva dos CP na graduação das escolas médicas. 10,12 Independentemente da especialização posterior, todo médico deve compreender os CP e como seus princípios se aplicam em diversos contextos da rede de atenção à saúde. É um tema que pode ser inserido a diversas disciplinas do curso médico: clínica, bioética, geriatria, cuidados intensivos, urgência e emergência, anestesiologia, oncologia, neurologia, pediatria, medicina de família, entre outros.…”
Section: Sobre Os Pré-requisitosunclassified